2010
DOI: 10.1007/s12686-010-9349-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic microsatellite DNA markers for the Amazonian catfish Pseudoplatystoma punctifer (Siluriformes: Pimelodidae)

Abstract: The large catfish Pseudoplatystoma punctifer has a high commercial value in the Amazon. Fifteen polymorphic microsatellite loci were isolated and characterized in 36-39 individuals of this species sampled at the Purus river (Amazon Basin). The number of alleles per locus ranged from 2 to 18 (average 7.4), the observed heterozygosity (H O ) from 0.025 to 0.972 and the expected heterozygosity (H E ) from 0.025 to 0.931. Two loci showed a Hardy-Weinberg Equilibrium deviation. No linkage disequilibrium was found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
3
6
0
Order By: Relevance
“…tigrinum corroborate those observed in other congeners, such as P. punctifer (SAULO-MACHADO et al 2010), P. reticulatum (PRADO et al 2014 and P. corruscans (REVALDAVES et al 2005) (Table 3).…”
Section: Resultssupporting
confidence: 84%
“…tigrinum corroborate those observed in other congeners, such as P. punctifer (SAULO-MACHADO et al 2010), P. reticulatum (PRADO et al 2014 and P. corruscans (REVALDAVES et al 2005) (Table 3).…”
Section: Resultssupporting
confidence: 84%
“…This value was within the range usually observed in other related species, such as P. corruscans in the Amazon basin and P. reticulatum in the Paraguay River Saulo-Machado et al, 2011; see also Carvalho et al, 2012 for a comparison of P. corruscans between Parana and São Francisco basins). However, in this study, F ST values tended to be slightly correlated with geographical distances according to Mantel test.…”
Section: Discussion Population Differentiation In P Punctifersupporting
confidence: 82%
“…Some previous studies investigated population genetic patterns in species of the genus Pseudoplatystoma, including Revaldaves et al (2005), who developed microsatellite primers for P. corruscans and tested its transferability to other species, including Pseudoplatystoma fasciatum (which is closely related, or even completely overlapped, with P. punctifer (see Buitrago-Suarez and Burr, 2007;Torrico et al, 2009;Carvalho-Costa et al, 2011). Saulo-Machado et al (2011) recently developed specific microsatellite markers for P. punctifer and described some genetic parameters within a local population. Pereira et al (2009) recently showed that a significant population differentiation occurred among local populations of P. corruscans, with an F ST around 8% and a significant spatial pattern in genetic differentiation according to Mantel test, by using 6 local populations (and interpreted such patterns as a consequence of homing behavior).…”
Section: For Reviews)mentioning
confidence: 99%
“…A total of six SSR markers were evaluated, four originally developed for Brachyplatystoma rousseauxi (Batista, Farias, Formiga-Aquino, Sousa, & Alves-Gomes, 2010) and two for Pseudoplatystoma punctifer (Saulo-Machado et al, 2011). Table 1 shows sequence information, annealing temperature, and GenBank accession number.…”
Section: Amplification Of Microsatellite Primersmentioning
confidence: 99%